Engineering and econometric interpretations of energy-capital complementarity - Berndt, Ernst R.; Wood, David O. (American Economic Review, 1979)
Econometric studies have recently shown an apparent contradictory evidence regarding substitution possibilities between energy (E) and capital (K). An analytical and empirical interpretation of E-K complementarity consistent with basic microeconomics and with the manufacturing process engineering evidence of E-K substitutability is presented. The notion of utilized capital is developed, and some of the seemingly disparate econometric findings are reconciled. The analysis emphasizes to the authors that care must be taken in interpreting and properly comparing alternative elasticity measures. 42 references. (MCW)